12 Rose Street : a Joanne Kilbourn mystery - Bowen, Gail, 1942- (Bowen, Gail, 1942- Joanne Kilbourn mysteries., 2015)
"Joanne's husband Zack is the leading progressive candidate in a neck-and-neck race, with the existing mayor, for Regina's top job. The tough campaigning is well underway when a disturbing threat disrupts the celebration for the opening of the Racette-Hunter Centre -- a project Zack has been spearheading, intended to benefit the impoverished community of North Central Regina. Joanne soon realizes that sinister interests are working behind the scenes of the election, and another savage act makes clear that someone will stop at nothing to maintain the status quo. The Shreve campaign perseveres, but when Zack's opponents share some shocking information about the past, the revelation sends Joanne reeling. As tensions around the election build, Joanne tries to hold herself together, keep her family intact, and get to the bottom of why a series of violent incidents, seemingly related to the mayoral race, all lead back to a mysterious property in North Central, 12 Rose Street."--